Methodological basis of state budget expenditure planning - Islamkulov, Alimnazar Khudjamuratovich; Umirzakova, Ezozakhan Sobirjan kizi (Science and Education, 2024)
The article examines the theoretical foundations of the formation of budget expenditures, their importance and classification, considers the essence and principles of budget planning, and analyzes the main methods of budget expenditure planning.